KEPRIBADIAN MEREK DAN IKATAN EMOSIONAL MEREK TERHADAP LOYALITAS MEREK TABUNGAN BANK UMUM SYARIAH - Sri Wahyuni (Jurnal Keuangan dan Perbankan, 2015)
Creating emotional brand attachment is a key branding issue in todays marketing world. One way to accomplishthis is to match the consumers self with brands personality and the consumers loyalty. This studyexamines the influence of brand personality, brand attachment toward brand loyalty in sharia banking inIndonesia. This quantitative research conducted on November 2013 until January 2014. On the basis ofempirical study of 8 sharia banking brands, the research were evaluated by 277 customers of sharia banking in5 big cities in Indonesia. Data were collected by a ten point Likert scale questionnaire consisting of statementsabout of brand personality, brand attachment toward brand loyalty. The data were analysed by StructuralEquation Modeling using AMOS. The findings of the study show that the implications of brands personalityfor consumers emotional brand attachment and brand loyalty are positive and significant. On a general level,brands personality has the greatest impact on emotional brand attachment. The authors discuss limitations ofthe scale and the boundary conditions important managerial and academic implications of these findings.